Samuel Plimsoll and the 1880 Carriage of Grain Legislation - Glover, William (The Northern Mariner / Le marin du nord, 2021)
Samuel Plimsoll was an advocate and agitator for improving safety at sea, best known for the load line mark on ships’ sides. He also campaigned for better safety of hazardous grain cargoes. But he suffered from an impetuous character, a lack of knowledge of the issues he championed and he frequently showed little regard for fact. How successful he was at achieving real legislative change? His grain cargoes agitation is compared with the earlier load line campaign which, it is argued here was completed without his input by others who understood the issues. Was the grain cargoes resolution any different? Porte-parole et fauteur de troubles, Samuel Plimsoll prônait l’amélioration de la sécurité en mer, surtout au moyen de lignes de charges sur les flancs des navires. Il a également fait campagne pour une meilleure sécurité des cargaisons de grains dangereuses. Mais il était aussi impétueux, affichait une ignorance au niveau des causes qu’il défendait et, souvent, accordait peu d’attention aux faits. Dans quelle mesure a-t-il réussi à obtenir de véritables changements législatifs? L’auteur compare les arguments de Plimsoll relatifs aux cargaisons de grains à sa campagne précédente sur les lignes de charges qui, aux dires de l’auteur, a été menée à bien sans son intervention par d’autres qui comprenaient les problèmes. La résolution de la question des cargaisons de grains s’est-elle avérée différente?